231k views
2 votes
Help quickly please I’m on a timer

Help quickly please I’m on a timer-example-1
User Jsw
by
4.7k points

2 Answers

3 votes

Answer:


C.(f+g)(x)=(5x^3+2x^2-4x-3)

Explanation:


We\ are\ given\ that,\\f(x)=5x^3+2x^2-7x+4\\g(x)=3x-7\\Hence,\\(f+g)(x)\\=f(x)+g(x)\\Hence,\\f(x)+g(x)=(5x^3+2x^2-7x+4)+(3x-7),\\ f(x)+g(x)=(5x^3+2x^2-7x+3x+4-7) \\f(x)+g(x)=(5x^3+2x^2-4x-3)\\Hence,\\(f+g)(x)=(5x^3+2x^2-4x-3)

User Karq
by
5.4k points
7 votes

Answer:

C.

Explanation:

Simply add the two functions.

5x³+2x²-7x+4

+ 3x-7

Everything with an exponent stays the same because there is nothing else with those exponents in the other function. So all you're doing is adding the -7x+4 and 3x -7.

-7x+3x = -4x

4 - 7 = -3

That leaves you with answer C:

5x³+2x²-4x-3

User Tankthinks
by
6.6k points